Aquatic Macroinvertebrates of Pinheirinho Stream, Parque do Basalto, Araraquara-SP: Subsidies for Local Conservation Strategies - Corbi, Juliano José (2009)
Aquatic fauna can be used as good indicators of the integrity of an aquatic environment. Because of some characteristics such as easiness of sampling and identification at family level and low general cost, the aquatic macroinvertebrates have been used as aquatic bioindicators, mainly in lotic environments. The present study had as main objective to analyze the macroinvertebrates of the Pinheirinho stream, located in the Basalto Park, with the purpose of investigating the conservation of the area. The macroinvertebrates were collected using a D-frame aquatic net (250 µm), including riffle and pools areas, during 5 minutes, as recommended by Fontoura (1985). Samples were taken to the laboratory, washed through a sieve with 0.21mm of mesh, selected on illuminated trays and fixed with 70% alcohol. The taxonomic identification was achieved at family level based on the available published data. In general, the results point to the necessity of environmental education in the Park, especially in its adjacent areas.